A rare case of incarcerated bochdalek diaphragmatic hernia in a pregnant lady - Ab Rashid, Islah Munjih; Din, Jiffre (Malaysian Medical Associations, 2010)
The occurrence of congenital diaphragmatic hernia in a pregnant adult is rare. In contrast to neonatal diaphragmatic hernias, most of the adult patients present with vague gastrointestinal symptoms mimicking other diseases hence the importance of high index of suspicion. We report a case of a young pregnant lady with congenital diaphragmatic hernia presenting with symptoms and clinical signs suggestive of acute pancreatitis. The patient had a laparotomy performed to reduce the hernial content and the diaphragmatic defect was successfully repaired.